1997
DOI: 10.1002/ijch.199700035
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited Quantum Dots. 6. Epitaxial Size Control in Cd(Se, Te) Nanocrystals on {111} Gold

Abstract: Size control in epitaxial Cd(Se,Te) quantum dots (QDs) electrochemically deposited on {HI} textured Au is achieved by mismatch tuning. The formation of QDs as a form of relaxation of heteroepitaxial strain energy is demonstrated. The increased lattice parameter resulting from incorporation of small amounts of Te in the CdSe lattice leads to reduced mismatch-induced strain energy and therefore larger QD size. While the QD interatomic spacings at the interface are shown to be unchanged due to the heteroepitaxy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The resulting 2:√7 supercell is characterized by a lattice mismatch of +0.13%. Similar structures have been observed in the electrodeposition of CdSe nanocrystals on Au(111) surfaces . The crystallites we observe are narrowly dispersed in diameter.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The resulting 2:√7 supercell is characterized by a lattice mismatch of +0.13%. Similar structures have been observed in the electrodeposition of CdSe nanocrystals on Au(111) surfaces . The crystallites we observe are narrowly dispersed in diameter.…”
Section: Resultssupporting
confidence: 84%
“…Finally, micrometer-scale STM images indicate the formation of nanometer-scale ZnS crystallites which appears to be driven by lattice-mismatch induced strain. Rubinstein and Hodes have observed similar morphologies when CdSe is electrodeposited on Au(111) from a solution of CdSO 4 and elemental Se . In addition, Resch et al reported in situ studies of ZnS grown by the successive ionic layer adsorption and reaction (SILAR) method showing similar islandlike features …”
Section: Introductionmentioning
confidence: 90%
“…This is also supported by recent experiments on the control of QD size by "misfit tuning" in Cd(Se,Te) QDs on Au. 47 When the same procedure is repeated with Pd substrate (4.1% mismatch for the same structure), a-CdSe QDs are obtained, with no apparent size limitation. These amorphous QDs exhibit the same short-range-order elements as the crystalline QDs on Au and consist of <2.5 nm ordered domains showing a preferred epitaxial relationship with the Pd substrate.…”
Section: Discussionmentioning
confidence: 97%
“…Increasing the QD lattice parameter by incorporation of small amounts of Te in the CdSe lattice leads to reduced mismatch-induced strain, and hence, to larger QD size, while partial substitution of Cd by Zn had the opposite effect. [4,6] Substituting {111} Au with {111} Pd (d {110} Pd = 0.2752 nm) as the substrate increases the lattice mismatch to 4.1 % (for the 3:2 ratio), resulting in diffraction-amorphous CdSe nanoparticles on top of an ultrathin CdSe film, both comprising extremely small (typically 1 nm) ordered CdSe clusters in an amorphous CdSe matrix. [3,5] Although the model assuming lattice mismatch as the major factor determining QD size has proven successful with most semiconductor/substrate pairs, in some cases, e.g., CdSe on Pd/ Au alloy and CdS on Pd, deviations from the expected behavior were observed.…”
Section: Introductionmentioning
confidence: 99%